The Teacher Problems in Implementing the Independent Curriculum in Islamic Religious Education Subjects - Sylva Rahmah Hafiz; Abdul Fattah Nasution; Widia Rahayu; Muliadi; Cahaya Maharani Sitompul (COMPETITIVE: Journal of Education, 2024)
This article explores the challenges faced by teachers in implementing the "Kurikulum Merdeka" (Independent Curriculum) in the subject of Islamic Religious Education (PAI). The study utilizes a literature review method to analyze relevant sources and gain a deeper understanding of the issues faced by teachers. The findings reveal several key challenges. Firstly, curriculum adaptation poses a major challenge, as it requires teachers to integrate Islamic teachings with the principles and demands of the Kurikulum Merdeka. Secondly, project-based learning within the curriculum demands additional effort from teachers in designing and managing active student involvement. Thirdly, holistic evaluation becomes complex for teachers as it involves assessing skills, attitudes, and religious knowledge. Additionally, resource limitations such as appropriate textbooks and learning materials aligned with the Kurikulum Merdeka hinder effective implementation. Insufficient training and support for teachers also influence the success of curriculum implementation. Recommendations include enhancing support and training for teachers, improving the availability of textbooks and learning resources, and fostering collaboration among teachers, schools, and communities to strengthen the implementation of the Kurikulum Merdeka.